RESPONSE OF ANALGESIA, SEDATION, AND RELAXATION OF KETAMINE AND PROPOFOL ANESTHESIA WITH XILASIN PREMEDICATION IN BALI CATTLE - Prihatiningsih, Nur Liliana Putri; Sudisma, I Gusti Ngurah; Pemayun, I Gusti Agung Gde Putra (Buletin Veteriner Udayana, 2022)
This study aims to determine the response of analgesia, sedation, and relaxation of the use xilasin premedication with anesthesia ketamine, propofol and their combination in bali cattle ( Bos sondaicus ). Bali cattle are used as many as 12 head which were divided into three treatment groups. This study used a completely randomized design with three treatments which are xilasin combination (0.1 mg) ketamine (2 mg), xilasin combination (0.1 mg) propofol (3 mg), xilasin combination (0.1 mg) ketamine (1 mg) and propofol (1.5 mg). The result of the research showed that ketamine and porofol anesthesia with xilasin premedication in bali cattle had a significant effect (P<0.05) on analgesia, sedation and relaxation responses. The average time for analgesia response is 2.5 – 12.5 minutes with analgesia duration of 5-17.5 minutes. For sedation response the average time of occurrence is 2.5-13.7 minutes with sedation duration of 5-13.75 minutes. The response time fot the occurrence of 5-12.5 minutes of relaxation with relaxation duration 2.5-23.75 minutes. In this study it can be concluded that the xilasin-ketamine-propofol combination is better fo bali cattle anesthesia becauses it produces a faster induction with a longer duration.